A Pneumatic Soft Glove System Based on Bidirectional Bending Functionality for Rehabilitation - Xiaohui Wang; Qinkun Cheng; Zhifeng Wang; Yongxu Lu; Zhaowei Zhang; Xingang Zhao (Biomimetics)
Stroke-related hand dysfunction significantly limits the ability to perform daily activities. Pneumatic soft gloves can provide rehabilitation training and support for individuals with impaired hand function, enhancing their independence. This paper presents a novel pneumatic soft robotic system for hand rehabilitation featuring bidirectional bending actuators. The system comprises a pneumatic soft glove and a pneumatic control platform, enabling various rehabilitation gestures and assisting with finger grasping. The main bending module of the pneumatic soft actuator features a three-stage cavity structure, allowing for a wider range of finger rehabilitation training gestures and greater bending angles. The reverse-bending module uses a trapezoidal cavity design to enhance the reverse-bending capability, effectively facilitating finger extension motion. The pneumatic control platform is simple to set up, but effectively controls the actuators of the soft glove, which enables both main and reverse bending. This allows individuals with hand impairments to perform various gestures and grasp different objects. Experiments demonstrate that the pneumatic soft glove has a measurable load capacity. Additionally, the pneumatic soft glove system is capable of executing single-finger movements, a variety of rehabilitation gestures, and the ability to grasp different objects. This functionality is highly beneficial for the rehabilitation of individuals with hand impairments.